2021
DOI: 10.1007/s00167-021-06813-3
|View full text |Cite
|
Sign up to set email alerts
|

Patellar dislocation is associated with increased tibial but not femoral rotational asymmetry

Abstract: PurposePatellar dislocation is associated with a range of anatomical abnormalities affecting the trochlea, extensor mechanism and the tibia. The relationship between patellofemoral instability and rotational abnormalities of the posterior condyles, trochlear groove and proximal tibia has not been adequately determined. This study aimed to identify the frequency and severity of anatomical risk factors to determine their relative contribution to patellofemoral instability. MethodsA retrospective morphological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…However, because hypoplasia of the femoral condyles and tibial torsional asymmetry of the tibial plateau have also been discussed as causative factors for anterior knee pain, we tried to identify other measurement methods of intra-articular knee rotation to define different landmarks and lines for comparison with patients with knee disorders. 14,15 Thus, the FEL and TECL were examined in relation to each other and to the DFC and DTH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because hypoplasia of the femoral condyles and tibial torsional asymmetry of the tibial plateau have also been discussed as causative factors for anterior knee pain, we tried to identify other measurement methods of intra-articular knee rotation to define different landmarks and lines for comparison with patients with knee disorders. 14,15 Thus, the FEL and TECL were examined in relation to each other and to the DFC and DTH.…”
Section: Discussionmentioning
confidence: 99%
“…However, because hypoplasia of the femoral condyles and tibial torsional asymmetry of the tibial plateau have also been discussed as causative factors for anterior knee pain, we tried to identify other measurement methods of intra-articular knee rotation to define different landmarks and lines for comparison with patients with knee disorders. 14,15 Thus, the FEL and TECL were examined in relation to each other and to the DFC and DTH. Tomczak et al 33 compared femoral torsional measurements using the method of Waidelich and Strecker in 44 patients and showed that there was no significant difference between MRI and computed tomography (CT) measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, not all segmental femoral torsion parameters were analyzed, such as neck and mid femoral anteversion. Second, the tibial morphology was not included, which has been demonstrated to be associated with LPD [ 35 ]. Third, measurements by MRI were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue structural abnormalities include contracture of the lateral retinaculum, laxity of the medial retinaculum, and injury or rupture of the medial patellofemoral ligament (MPFL); bony structural abnormalities include trochlear dysplasia, tibial external rotation, increased femoral anteversion, lateralization of the tibial tuberosity, and patella alta. 16,26,32,53,64 Nonoperative treatment has long been considered the standard of care, 4,6 whereas operation is now recommended for recurrent patellar dislocations, for osteochondral fractures with free bodies, and for those whose nonoperative interventions have failed. 63 Scientometric analysis is a tool for mapping identified publication records and enabling the study of mathematical patterns in the literature, and it is a method for assessing and predicting research trends in specific fields.…”
mentioning
confidence: 99%